BUZU: Retrieving public transportation data for sonification - Arango, Julian J.; Astorga, Esteban Viveros; Iazzetta, Fernando; Figueiró, Cristiano (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2019.10420, 2019)
This paper discusses the conception, design and exhibition of BUZU, an audiovisual installation that generates an auditory image of the São Paulo bus transportation system. BUZU makes perceptible information of both the system’s planning and behavior during a particular week in October 2017. The work is an artistic outcome of the InterSCity project, an inter-institutional research initiative concerning the Future Internet and the Smart Cities. Along with the discussion of the BUZU creation process we will examine mining and processing strategies related to the sonification of big data, the data-to-sound mapping methods, the auditory structure for displaying the material and the public exhibition of the work in the context of an artistic event.